2014
DOI: 10.1179/2045772314y.0000000271
|View full text |Cite
|
Sign up to set email alerts
|

The influence of shoulder pain on functional limitation, perceived health, and depressive mood in patients with traumatic paraplegia

Abstract: Objective: To assess whether functional activity, perceived health, and depressive symptoms differ between individuals with traumatic paraplegia with and without shoulder pain. Design: Cross sectional and comparative investigation using the unified questionnaire. Setting: Neural Regeneration and Repair Division unit of Taipei Veterans General Hospital in Taiwan. Participants: Seventy-six patients with paraplegia (23 with and 53 without shoulder pain) who had experienced spinal cord injury at American Spinal In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Only a few studies provided separate demographic information for participants with and without SCI pain. 26,29,38 Participants reported experiencing neuropathic (at-level and below-level) pain and/or nociceptive (musculoskeletal, visceral) pain. The two acute SCI studies reported ongoing pain from injury onset.…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies provided separate demographic information for participants with and without SCI pain. 26,29,38 Participants reported experiencing neuropathic (at-level and below-level) pain and/or nociceptive (musculoskeletal, visceral) pain. The two acute SCI studies reported ongoing pain from injury onset.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…This resulted in a final sample of 16 independent studies. 11,18,24,26,[29][30][31][32][33][34][35][36][37][38][39][40] Data extraction and organisation…”
Section: Psychosocial Aspects Of Sci Pain J Tran Et Almentioning
confidence: 99%
“…Age, gender, injury level, injury duration and the number of times moving from wheelchair onto bed and back factors which reported in previous research affect shoulder pain (23)(24)(25). Studies also indicated that the time passed after the injury and transferring from wheelchair to bed and back were considered as influential factors on shoulder pain (11,26). In a systematic review carried out in 2014, shoulder pain prevalence among quadriplegic patients has been reported to be more frequent in general.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, it is not surprising that shoulder pain and dysfunction is very common in these patients [20]. Although loss of shoulder function has a significant negative impact on the independence and quality of life of these patients [9], there are few studies investigating the treatment of shoulder disorders in this population. Surgical treatment of shoulder disorders in wheelchair‐dependent individuals is a challenging scenario for both patients and surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the prevalence of shoulder disorders in wheelchair-dependent patients is greater than in the general population [1][2][3][4][5][6]. Shoulder pathology has a substantial negative impact on patients' autonomy, quality of life, and physical, and psychological and social well-being [7][8][9]. Hence, investigations on the treatment of shoulder pain and dysfunction in wheelchairdependent patients are very relevant.…”
Section: Introductionmentioning
confidence: 99%